2016
DOI: 10.1016/j.talanta.2016.05.032
|View full text |Cite
|
Sign up to set email alerts
|

Determination of halogens and sulfur in high-purity polyimide by IC after digestion by MIC

Abstract: In this work, a method for sample preparation of high-purity polyimide was proposed for halogens and sulfur determination by ion chromatography (IC) with conductivity detection and, alternatively, by inductively coupled plasma mass spectrometry (ICP-MS). A relatively high polyimide mass (600mg) was completely digested by microwave-induced combustion (MIC) using 20bar of O2 and 50mmolL(-1) NH4OH as absorbing solution. These conditions allowed final solutions with low carbon content (<10mgL(-1)) and suitable pH … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Moreover, well diluted absorbing solutions also play an important role in obtaining a suitable solution for halogen absorption and further determination by ICP-MS. 40,120,121,127,129,132 Despite MIC having presented success when digesting organic/combustible matrices, it has not been applied to the same extent for inorganic samples. However, recent applications have demonstrated that, with some changes in the original MIC method (e.g., addition of an combustion aid), it can also be applied for this type of matrix.…”
Section: Sample Preparation Methods For Further Halogen Determinatimentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, well diluted absorbing solutions also play an important role in obtaining a suitable solution for halogen absorption and further determination by ICP-MS. 40,120,121,127,129,132 Despite MIC having presented success when digesting organic/combustible matrices, it has not been applied to the same extent for inorganic samples. However, recent applications have demonstrated that, with some changes in the original MIC method (e.g., addition of an combustion aid), it can also be applied for this type of matrix.…”
Section: Sample Preparation Methods For Further Halogen Determinatimentioning
confidence: 99%
“…78 A different strategy that can also be used for halogen determination is isotope dilution (ID)-ICP-MS. This approach uses an enriched isotope of the analyte as an IS, and the isotope ratios are measured by ICP-MS. 85 In this sense, 127 I determination has been performed using 129 I as IS. 86 Iodine has only one natural stable isotope at m/z 127, but samples can also be spiked with a known amount of 129 I, a long-lived radionuclide.…”
Section: Internal Standards and Isotope Dilution For Halogen Determmentioning
confidence: 99%
“…Analysis of halogens in organic matrices usually are conducted by decomposition of the samples or salt extraction and further analysis as inorganic ions (e.g., chlorides) by ion chromatography (IC) [ 5 , 6 , 7 , 8 ], potentiometric titration [ 9 , 10 ], and inductively coupled plasma mass spectrometry (ICP-MS) apparatus with special equipment [ 5 , 6 , 10 , 11 , 12 , 13 , 14 , 15 ]. Traditional acid digestion is undesirable for this purpose due to possibility of analyte losses by volatilization and chlorine liberation.…”
Section: Introductionmentioning
confidence: 99%
“…The evolved chlorine has to be absorbed in alkaline solution or solid (e.g., sodium carbonate) [ 7 , 8 , 16 , 17 , 18 , 19 , 20 ]. In such a case, special equipment is used for sample decomposition without volatile analyte loss—Schoniger combustion flask, combustion tubes, microwave-induced combustion system (MIC) [ 7 , 8 , 18 , 19 ], or bombs (Parr bomb) [ 5 ]. Fusion with sodium carbonate or pyrohydrolysis may also be applied [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Besides the classical methods for determination of chloride ions such as gravimetric, volumetric or colorimetric methods, chlorine determination in different samples and chemical forms can be accomplished by a variety of analytical techniques including potentiometry, total reflection X-ray fluorescence, neutron activation analysis or inductively coupled plasma mass/optical emission spectrometry [3]. When aiming at analyzing solid samples, however, most of these analytical techniques generally require extensive sample treatment before analysis [4], which involves high risk of analyte losses and/or contamination and require longer analysis times. In these situations, the use of direct solid sample analysis could help overcoming these problems [5][6][7].…”
Section: Introductionmentioning
confidence: 99%